Synthesis and characterization of a novel fluorene-based polyquinoline - Son, S.-W.; Jung, S.-H.; Kim, J.-K.; Cho, H.-N. (American Chemical Society, Polymer Preprints, Division of Polymer Chemistry, 2002)
[No abstract available]